Spin transport properties of triarylamine-based nanowires - SANVITO, STEFANO (My University, 2014)
Triarylamine-derivatives can self-assemble upon light irradiation in one-dimensional nanowires with remarkable hole transport properties. We use a combination of density functional theory and Monte Carlo simulations to predict the nanowires spin-diffusion length. The orbital nature of the nanowires valence band, namely a singlet π-like band localised on N, suggests that hyperfine coupling may be weak and that spin–orbit interaction is the primary source of intrinsic spin relaxation. Thus, we construct a model where the spin–orbit interaction mixes the spins of the valence band with that of three degenerate lower valence bands of sp2 nature. The model includes also electron–phonon interaction with a single longitudinal mode. We find a room temperature spin-diffusion length of the order of 100 nm, which increases to 300 nm at 200 K. Our results indicate that triarylamine-based nanowires are attractive organic semiconductors for spintronics applications.
PUBLISHED
Keywords: Nanowires; Nanoscience & Materials